1987
DOI: 10.1111/j.1600-051x.1987.tb00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Some periodontal tissue reactions to orthodontic tooth movement in monkeys

Abstract: The purpose of the experiment reported was to study soft tissue changes at teeth which were orthodontically moved into areas with varying thickness and quality of periodontal tissues. The maxillary central incisors and first premolars in 5 adult monkeys were used as experimental teeth. 6 months prior to the start of the orthodontic treatment phase, the maxillary second premolars were extracted. By surgical means, areas with varying width of the keratinized gingiva were established in the incisor and premolar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
174
1
34

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(223 citation statements)
references
References 25 publications
6
174
1
34
Order By: Relevance
“…[6][7][8][9][10] Ackerman and Proffit introduced the concept of the "envelope of discrepancy," which graphically shows the extent of changes possible with orthodontic tooth movement alone, with orthopedic or functional appliance therapy for growth modification, and with orthognathic surgery in combination with orthodontic treatment. 7,11 Accordingly, it is traditionally thought that the amount of changes possible for the maxillary incisors with orthodontic treatment alone are approximately 7, 2, 4, and 2 mm for retraction, protraction, extrusion, and intrusion, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Ackerman and Proffit introduced the concept of the "envelope of discrepancy," which graphically shows the extent of changes possible with orthodontic tooth movement alone, with orthopedic or functional appliance therapy for growth modification, and with orthognathic surgery in combination with orthodontic treatment. 7,11 Accordingly, it is traditionally thought that the amount of changes possible for the maxillary incisors with orthodontic treatment alone are approximately 7, 2, 4, and 2 mm for retraction, protraction, extrusion, and intrusion, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…There is a positive correlation between buccal movement of teeth and bone dehiscence. (32) concluded that buccal tooth movement can increase the distance between BACL and cement-enamel junction. In our study, BACL increased statistically significantly in both groups that means a decrease in crestal level.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24][25] As a result, mediators that are effective in bone resorption and osteoclastic activity are excreted. 26 The application of force mechanics may lead to the risk of trauma, edema, and infection. To eliminate these probabilities, one dose of prophylactic antibiotic was administered to all rats.…”
Section: Discussionmentioning
confidence: 99%